Prevalence of smartphone addiction and its related factors among pre-clinical students at IIUM Kuantan Campus 2016 - Pasi, Hafizah; Mohd Rus, Razman; Ab Rahman, Jamalludin; Abd. Aziz, Karimah Hanim; Nasreen, Hashima E; Yusof, Muhammad Zubir (2016)
Background. Smartphone addiction is a phenomenon whereby a person is unable to cut down the smartphone use and it triggers physiological stress because of overuse and leads to anxiety when their smartphones are not with them. Medical students are among the population developing smartphone addiction. The aim of this study is to determine the prevalence of smartphone addiction and its related factors among preclinical students at IIUM Kuantan Campus.